Increasing Incidence of Young-Onset Colorectal Carcinoma A 3-Country Population Analysis. Issue 7 (July 2020) - Chittleborough, Timothy J.; Gutlic, Ida; Pearson, John F.; Watson, Angus; Bhatti, Lesley A.; Buchwald, Pamela; Potter, John D.; Wakeman, Christopher; Eglinton, Tim; Frizelle, Frank
Abstract : BACKGROUND: The overall incidence of colorectal carcinoma is declining in Western populations; however, single country series demonstrate an increase in young-onset (<50 years) colorectal carcinoma. OBJECTIVE: The purpose of this study was to determine whether the pattern of increasing incidence of young-onset colorectal carcinoma is consistent across 3 Western populations. DESIGN: This is a population incidence study. SETTINGS: National cancer registries of New Zealand, Sweden, and Scotland were used. PATIENTS: The incidence of colorectal carcinoma was calculated from population data for 3 countries over 2 to 4 decades. MAIN OUTCOME MEASURES: The incidence of colorectal carcinoma was measured. Incidence rate ratios were determined and data were stratified by subsite (colon versus rectum), sex, and age (<50, 50–79, and ≥80 y). RESULTS: Overall colorectal carcinoma rates declined in New Zealand, remained stable in Scotland, and increased in Sweden. In all 3 populations, there was an increasing incidence of rectal carcinoma in those aged <50 years. Young-onset rectal carcinoma increased in New Zealand (1995–2012: incidence rate ratio = 1.18 (men) and 1.13 (women)), with declining incidence in all other age groups. Colon carcinoma did not increase in the population aged <50 years, with the exception of distal colonic carcinoma in men. Overall, rectal carcinoma incidence increased (1970–2014) in Sweden; however, increases in those <50 years of age exceeded increases in other age groups (incidence rate ratio = 1.14 (males) and 1.12 (females)). Distal colon carcinoma increases were most marked in the population aged <50 years. In Scotland (1990–2014), young-onset rectal carcinoma incidence increased (incidence rate ratio = 1.23 (males) and 1.27 (females)), with a smaller increase in colon carcinoma. LIMITATIONS: Limitations include its registry-based, population incidence research. CONCLUSIONS: This study shows an increase in young-onset rectal carcinoma in 3 national populations; this observation may provide a focus for looking at the role of environmental influences on the etiology of this increase and therefore to explore strategies for prevention. See Video Abstract at http://links.lww.com/DCR/B194 . AUMENTO DE LA INCIDENCIA DE CARCINOMA COLORRECTAL DE INICIO JOVEN: UN ANÁLISIS DE POBLACIÓN DE TRES PAÍSES: ANTECEDENTES: La incidencia global de carcinoma colorrectal está disminuyendo en las poblaciones occidentales. Sin embargo, las series de un solo país demuestran un aumento en el carcinoma colorrectal de inicio joven (pacientes menores de 50 años). OBJETIVO: Determinar si el patrón de incidencia en aumento de carcinoma colorrectal de inicio joven es consistente en tres poblaciones occidentales. DISEÑO: Estudio de incidencias de población en tres países. ENTORNOS CLINICOS: Registros nacionales de cáncer de Nueva Zelanda, Suecia y Escocia. PACIENTES: la incidencia de carcinoma colorrectal se calculó a partir de datos de población de tres países durante dos o a cuatro décadas. PRINCIPALES MEDIDAS DE VALORACION: Incidencia de carcinoma colorrectal. Se determinaron las tasas de incidencia y los datos se estratificaron por subsitio (colon versus recto), además de sexo y edad (<50, 50-79 y ≥ 80). RESULTADOS: las tasas generales de carcinoma colorrectal disminuyeron en Nueva Zelanda, se mantuvieron estables en Escocia y aumentaron en Suecia. En las tres poblaciones, hubo una incidencia creciente de carcinoma rectal en pacientes menores de 50 años. El carcinoma rectal de inicio juvenil aumentó en Nueva Zelanda (1995-2012): tasa de incidencia de 1, 18 [varones] y 1, 13 [mujeres], con una disminución de la incidencia en todos los demás grupos de edad. El carcinoma de colon no aumentó en la población de < 50 años, con la excepción del carcinoma de colon distal en hombres. En general, la incidencia de carcinoma rectal aumentó (1970-2014) en Suecia; sin embargo, los aumentos en aquellos de <50 años excedieron los aumentos en otros grupos de edad: tasa de incidencia 1.14 [hombres] y 1.12 [mujeres]. Los aumentos del carcinoma de colon distal fueron más marcados en la población de < 50 años. En Escocia (1990-2014), la incidencia de carcinoma rectal de inicio juvenil aumentó: relación de tasa de incidencia 1.23 [hombres] y 1.27 [mujeres], con un aumento menor en el carcinoma de colon. LIMITACIONES: Investigación de incidencia poblacional basada en registros nacionales. CONCLUSIONES: Este estudio muestra un aumento en el carcinoma rectal de inicio joven en tres poblaciones nacionales. Esta observación puede indicar un enfoque para la examinación de influencias ambientales en la etiología de este aumento y, por lo tanto, explorar estrategias para la prevención. Consulte Video Resumen en http://links.lww.com/DCR/B194 . ( Traducción—Dr Adrián Ortega )